Precambriam Organic Compounds from the Ketilidian of South-West Greenland, Part II. - Lam, Jørgen; Raunsgaard Pedersen, K. (Meddelelser om Grønland, 1968)
Results of work on organic compounds extracted from well preserved Kelilidian sedimentary rocks from South-West Greenland about 2000 m.y. old are presented. The organic material was obtained from a dolomitic layer with great numbers of the globular fossil Vallenia erlingi RAUNSGAARD P EDERSEN. Of the two samples examined one sample contains normal and branched alkanes with chain lengths from C10 to C20 , various aromatic hydrocarbons including benzene derivatives and naphthalenes. The other sample contains normal and branched alkanes with chain lengths from C10 to C32 and it did not show any aromaticity. but methyl esters of palmitic acid and other fatty acids are present. The presence of these compounds provides further evidence of the organic origin of Vallenia.